Feasibility and acceptability of computer based online certifcation program for frontline community health workers of Wardha district, India - Patil, Manoj S; Gaidhane, Abhay M; Telrandhe, Shital; Zahiruddin, Quazi Syed; Jadhav, Navnita (Asian Journal of Medical Sciences, 2017)
Background: In India, different types of Frontline Community Health Workers are recruited under different departments and health programmes. These include Anganwadi Workers (AWW) under ICDS, ASHA and ANMs under NRHM and health services. Training and recruitment of this staff cadre is an ongoing process. Most of the trainings are aimed at improving the knowledge and skills. A set of test is needed to assess the post training knowledge of trainees which should be feasible, acceptable and easy to administer. Team of Health Experts from DMIMSU, Wardha has developed such specifc Computer based online certifcation tests which were administered to selected Frontline Community Health Workers engaged with DMIMSU. This study was conducted to assess the feasibility and acceptability of these tests. Aims and Objectives: Team of Health Experts from DMIMSU,Wardha has developed specifc Computer based online certifcation tests which were administered to selected Frontline Community Health Workers engaged with DMIMSU. This study was conducted -1] To assess the feasibility and acceptability of Computer based online certifcation tests for frontline workers. 2] To assess the scope for generalization of these tests to entire frontline health cadre of the district. Materials and Methods: Data was collected from 30 randomly selected Frontline Health Workers who were engaged in Community Outreach Activities/Projects of DMIMS and had undergone trainings and Online Certifcation tests. Questionnaire with Likert type scoring scale was administered. Data was compiled in MS Excel and Weighted Means and proportions of responses towards agreement and disagreement were calculated. Results: Average Weighted Mean was 4.07 showing Strong Agreement towards the feasibility and acceptability. Only 10.3% participants showed disagreement towards the feasibility and acceptability of this test whereas 89.7% participants showed agreement and among them, 47.67% showed strong agreement towards the feasibility and acceptability of this test. Conclusion: These tests were found quite feasible and well accepted by Frontline Health Workers. Similar tests should be made compulsory for all Frontline Health Workers Cadre and their performance in tests should be linked to provisions of incentives and seniority benefits. Asian Journal of Medical Sciences Vol.8(2) 2017 82-85